(untitled) (Communication & Society, 2019)
This paper analyses the information sources used in a large corpus of news items published in Spanish printed newspapers between 1618 and 1635. The initial aim is to determine how information credibility was constructed in both historical and rhetorical terms. To this end, the rhetorical construction of credibility in the news stories are analysed by focusing on the information sources that these reveal or conceal. And in order to determine whether or not these sources were deliberately concealed, the frequency with which ‘on deep background’ attribution appears is examined. The methodological approach on which this study is based is Historical News Discourse, which applies the conclusions and methods of critical discourse analysis to newspapers of the past, in addition to contextualising and explaining the results in terms of journalism history and communication approaches (Conboy, Brownlees and Broersma, among others). In this work, we contend that the discourse analysis of the first printed newspapers is essential for gaining further insights into how the journalistic profession consolidated its position in Spain thanks to a new form of auctoritas based on discourse competence. The gazetteer or journalist emerged as a new kind of writer, whose credibility and reputation depended on his ability to access, organise and reveal –according to rhetorical patterns recognisable to readers– the information sources available to him.